Associated factors for discussing advance directives with family physicians by noncancer outpatients in Japan. (20th February 2019) - Hamada, Shuhei; Haruta, Junji; Hamano, Jun; Maeno, Takami; Maeno, Tetsuhiro
Abstract: Background: Advance directives (ADs) are seldom discussed between primary care physicians (PCPs) and their patients, especially those with noncancer diseases. The aim was to identify the factors associated with discussing AD by noncancer patients with their physicians. Methods: This cross‐sectional study was conducted in a hospital or clinic from October to December 2017. Physicians chose eligible noncancer patients aged 20 years or older to respond to an anonymous self‐completed questionnaire inquiring about the objective variable "I want to discuss AD with my doctor, " as well as basic characteristics, and facilitators and barriers to discussing AD identified in previous studies. The physicians responded to a survey comprising the Palliative Performance Scale (PPS) and inquiring about the disease category for each patient. Data were analyzed using binomial logistic regression analysis. Results: A total of 270 patients (valid response rate, 79.6%) were included. Multivariate analysis identified a period of visit to the study site ≥ 3 years (odds ratio [OR], 2.07; 95% confidence interval [CI], 1.05‐4.10), physicians who are very good at taking care of patients' disease (OR, 12.68; 95% CI, 1.12‐143.22), and patients' worry about their quality of life (QOL) in the future (OR, 2.69; 95% CI, 1.30‐5.57) as facilitators for discussing AD with physicians, and PPS ≤ 90 (OR, 0.51; 95% CI, 0.26‐0.98) as a barrier. Conclusions: Our study indicates that patients' future QOL concerns, a long period of visit to a hospital, and the presence of physical symptoms were associated with the willingness of noncancer patients to discuss AD with PCPs. Abstract : Among noncancer patients who visited an outpatient hospital or clinic in a primary care setting, willingness to discuss AD with their physicians was significantly positively correlated with a period of visit to the study site of ≥3 years, belief that "My doctor is very good at taking care of my disease, " and feelings of "I worry about my quality of life in the future" and was significantly negatively correlated with a PPS score of ≤90.